2022
DOI: 10.1111/1471-0528.17041
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life from cytoreductive surgery in advanced ovarian cancer: Investigating the association between disease burden and surgical complexity in the international, prospective, SOCQER‐2 cohort study

Abstract: Objective: To investigate quality of life (QoL) and association with surgical complexity and disease burden after surgical resection for advanced ovarian cancer in centres with variation in surgical approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…From the magnitude of effect sizes in comparisons of 0 cm versus larger amounts of RD (where there were sufficient evidence available for a give RD threshold), it seems that if RD cannot be limited to an optimal level then the surgeon could potentially prioritize their focus on morbidity and quality of life (QoL). The results of the SOCQER-2 102 study commissioned by NICE, assessed QoL in women undergoing standard or extensive surgery after primary surgery in advanced EOC. This study found no important differences in global QoL scores measured across 6 weeks, 6 months, and 12 months postsurgery in varying complexities of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…From the magnitude of effect sizes in comparisons of 0 cm versus larger amounts of RD (where there were sufficient evidence available for a give RD threshold), it seems that if RD cannot be limited to an optimal level then the surgeon could potentially prioritize their focus on morbidity and quality of life (QoL). The results of the SOCQER-2 102 study commissioned by NICE, assessed QoL in women undergoing standard or extensive surgery after primary surgery in advanced EOC. This study found no important differences in global QoL scores measured across 6 weeks, 6 months, and 12 months postsurgery in varying complexities of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…We found that in cohorts balanced for age and morphology, centres with greater utilization of URS increased the proportion of patients treated surgically compared to centres that mainly practiced low complexity surgery. However, centres practicing mainly intermediate SCS were most likely to deliver both surgery and chemotherapy; this may reflect greater use of surgery for palliation, e.g., bowel obstruction in high SCS centres but may also reflect challenges in delivery of chemotherapy after ultra-radical surgery, although this was not observed in the UK-based SOCQER2 study [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consecutive participants were identified prior to surgical treatment and recruited between September 2015 and September 2016 and followed up to 24 months. Results from the study and description of variation in surgical practice across centres have been previously reported [ 9 ]. This paper describes population level outcomes for Stage3/4 and unstaged ovarian cancer patients managed at the 11 participating centres in England.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgery frequently involves liver mobilization, excision of diaphragmatic peritoneum, bowel resection, and splenectomy. Mortality ranges from 1% to 3% with anastomotic leakage being a key contributor 1…”
mentioning
confidence: 99%